Neonatal Bone Disorders - Saraff, Vrinda; Nadar, Ruchi; Shaw, Nick (Frontiers in Pediatrics, 2021)
Neonatologists care for newborns with either an antenatal suspicion or postnatal diagnosis of bone disease. With improved ultrasound imaging techniques, more cases of neonatal bone disorders are identified antenatally and this requires further diagnostic/molecular testing either antenatally or soon after birth for confirmation of the diagnosis and facilitating appropriate management thereafter. Prompt diagnosis is vital in certain conditions where initiation of treatment is time critical and life saving. We outline an approach to diagnosis, investigation and management of a neonate with a suspected bone disorder